Growing up after the GFC: responsibilisation and mortgaged futures. Issue 1 (2nd January 2017) - Kelly, Peter
ABSTRACT: In this paper I argue that in the aftermath of the Global Financial Crisis of 2008–2009 young people, certain populations of young people in particular, are being made to bear a heavy burden, carry significant responsibilities for re-imagining their lives as a enterprise – an enterprise in which an investment in education and training and work increasingly looks like a mortgaging of an uncertain future. In mortgaging their future, many young people are confounded by the possibility of repaying this debt, or of leveraging it into a life that was promised them if only they stayed in education and training, if only they got a job, if only they studied and worked hard, and had an eye to the future. The paper will explore some of the characteristics of the self as enterprise, the challenges and opportunities that shape the fields of possibilities from which this self emerges, and which require us to practise our freedom in particular, always limited, ways and to carry responsibilities for more and more aspects of our lives, in circumstances that mostly escape our differing, individual abilities and capacities to shape these circumstances.